О времени сооружения кургана Беш-Оба IV/3 Аккайского (Белогорского) курганного могильника - Колтухов, С.Г. (Археологія і давня історія України, 2019)
Заметка посвящена обоснованию мнения о сооружении во второй—третьей четверти IV в. до
н. э. Кургана 3, топографической группы царского
кургана IV, расположенного на г. Беш-Оба в Предгорном Крыму. The article is devoted to the justification of the opinion
on the construction in the second and third quarters
of the 4th cent. BC. Mound 3, the topographic group of
the royal mound IV, located on the town of Besh-Oba in
the Piedmont Crimea. The Besh Oba IV / 3 burial mound was a part of
Besh Oba IV burial mound, which was built in the end
of the second to the third quarter of the 4th cent. BC.
Analysis of the funeral equipment from the floor of the burial chamber in the crypt of the mound 3, allows to
synchronize the royal burial mound IV and the burial mound 3. It makes us face the fact that the inlet «collective
» burials in the burial chamber of the burial mound crypt 3, belong to a later time than the crypt and date
back mainly as 2nd cent. BC. This conclusion confirms the correctness of the dating of the Besh-Ob IV group
of burial mounds, which was previously suggested by S. G. Koltukhov, and S.V. Polin. Consequently, it receives
an additional confirmation of the opinion that the entire aristocratic Scythian burial mound, located on
the mountains of Ak-Kaya and Besh-Ob, can be related to the second and third quarters of the 4th cent. BC.